Determination of Optimum Quantity of Cassava Peel Ash (CPA) as Partial Replacement of Cement for Maximum Concrete Strength and its Cost Analysis. - Nasasira, Johnson (Kabale University, 2024)
This research titled “Determination of optimum quantity of cassava peel ash (CPA) as partial replacement of cement for maximum concrete strength and its cost analysis” aims at the utilization of cassava peels which are the waste product of cassava processing as a partial replacement of ordinary Portland cement. Cassava peel samples were collected from Bikurungu cassava millers’ factories in Rukungiri district, southwestern Uganda. The cassava peels were sundried and burnt into ash in the furnace at 700-800oc and their chemical and physical properties were studied using the X-ray Fluorescence method which was found to contain elements such as calcium dioxide 85.677%, iron (iii) oxide 5.662%, silicon dioxide 3.517%, potassium oxide 1.731%, aluminum oxide 1.515% manganese(ii) oxide 0.803%, phosphorous pent oxide 0.456%, titanium oxide 0.310%, chromium (ii) oxide 0.143%, and magnesium oxide 0.109%. blended pastes containing OPC and 45 cubes were caster with cassava peel ash (CPA) at different percentage replacement, 0%, 5%, 10%, 15%, and 20% were investigated for consistency, initial and final setting time for the blended paste CPA- OPC pastes and dry density of cubes and compressive strength of grade 25 (C25) Concrete. The results of the study show that the optimum percentage of CPA is 10% replacement of OPC with cassava peel ash gave 24.4 N/m2 which is the maximum concrete strength achieved after partially replacing OPC with cassava peel ash (CPA)